2006
DOI: 10.1080/03014460600802551
|View full text |Cite
|
Sign up to set email alerts
|

The second to fourth digit ratio and asymmetry

Abstract: Our data show that both low 2D:4D (a marker of high prenatal testosterone) and high 2D:4D (a marker of high prenatal oestrogen) are associated with elevated levels of asymmetry and this relationship applies particularly to finger asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…The directional asymmetry of digit ratio provides information about the sensitivity of the limbs to hormonal exposure (Brown et al, 2002b;Manning et al, 2006). It has been reported that, in humans, directional asymmetry is grater in males (Williams et al, 2000;Manning, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The directional asymmetry of digit ratio provides information about the sensitivity of the limbs to hormonal exposure (Brown et al, 2002b;Manning et al, 2006). It has been reported that, in humans, directional asymmetry is grater in males (Williams et al, 2000;Manning, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a second study indicated a curvilinear relationship between body asymmetry and 2D:4D. That is, both low 2D:4D and high 2D:4D were associated with elevated levels of asymmetry, especially in the fingers [83]. However, it has been argued that most of the observed correlations between 2D:4D and degrees of asymmetry are likely to be statistical artifacts and predictions can be formulated contrary to the observed patterns [79,84,85].…”
Section: Human Studiesmentioning
confidence: 66%
“…However, it has been argued that most of the observed correlations between 2D:4D and degrees of asymmetry are likely to be statistical artifacts and predictions can be formulated contrary to the observed patterns [79,84,85]. Because the same variables (i.e., digits) were used as both dependent and independent variables, U-shaped associations would be expected [83] even in the absence of any association between 2D:4D and FA, rendering the results spurious [79,84,85]. These conjectures were further corroborated by the observation that 2D:4D in deceased human fetuses and young children correlate neither with finger FA nor any other trait asymmetries [79].…”
Section: Human Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Except for hand width, we do consider these traits when presenting data for single traits rather than composite FA. Manning et al [33] advise against using indirect finger measurements in studies of symmetry. However, several lines of evidence suggest that the reliability of finger measurements was not decreased by switching to indirect measurements in later years.…”
Section: Subjects and Measurementsmentioning
confidence: 99%